2013
DOI: 10.1017/s0020589313000109
|View full text |Cite
|
Sign up to set email alerts
|

Building a Global Redress System for Low-Value Cross-Border Disputes

Abstract: This article examines UNCITRAL's draft Rules for Online Dispute Resolution (ODR) and argues that in low-value e-commerce cross-border transactions, the most effective consumer protection policy cannot be based on national laws and domestic courts, but on effective and monitored ODR processes with swift out-of-court enforceable decisions. The draft Rules propose a tiered procedure that culminates in arbitration. Yet, this procedure neither ensures out-of-court enforcement, nor does it guarantee compliance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Academic literature on CBEC is still in its infancy and lacks in-depth coverage. Some studies have looked into specific elements such as designing CBEC logistics (Gessner & Snodgrass, 2015), taxation implementation (Azam, 2012), and CBEC-related dispute resolution (Cortés & de la Rosa, 2013;Rule, Rogers, & del Duca, 2010). Little research exists looking into the challenges and reasons for the rise of this new market access channel and why foreign brands select this new mode of entry and the challenges they face.…”
Section: Defining Cross Border E-commercementioning
confidence: 99%
“…Academic literature on CBEC is still in its infancy and lacks in-depth coverage. Some studies have looked into specific elements such as designing CBEC logistics (Gessner & Snodgrass, 2015), taxation implementation (Azam, 2012), and CBEC-related dispute resolution (Cortés & de la Rosa, 2013;Rule, Rogers, & del Duca, 2010). Little research exists looking into the challenges and reasons for the rise of this new market access channel and why foreign brands select this new mode of entry and the challenges they face.…”
Section: Defining Cross Border E-commercementioning
confidence: 99%
“…Other studies have described challenges in designing a global consumer ODR system [26] and showed that effective dispute settlement is one way to enhance consumer confidence in cross-border purchases made via the Internet [27]. However, Cortés and de la Rosa [28] argued that in low-value e-commerce cross-border transactions, the most effective consumer protection policy could not be based on national laws and domestic courts. Lin et al [29] showed that swift action following a dispute in cross-border e-commerce could help restore trust in the e-tailer.…”
Section: Online Resolution Systemsmentioning
confidence: 99%
“…Focusing on trust is a result of applying to the Internet the traditional ADR perspective in which interests and private gains and losses prevailed over other public automated/assisted negotiation between the parties without a human neutral, which may include blind-bidding techniques; (2) mediation/conciliation; and (3) arbitration leading to a decision which can be enforced". 6 After analyzing UNCITRAL's draft Rules for ODR, Cortés and Esteban de la Rosa contend [19]: "low-value e-commerce cross-border transactions, the most effective consumer protection policy cannot be based on national laws and domestic courts, but on effective and monitored ODR processes with swift out-of-court enforceable decisions".…”
Section: Odr Ethical Principles and The Redefinition Of The Global Pmentioning
confidence: 99%